Taking the temperature of the United States public regarding microbiome engineering - Cummings, Christopher; Landreville, Kristen D.; Kuzma, Jennifer (Frontiers in Public Health, 2024)
This paper presents the first representative survey of U.S. adults’ opinions on microbiome engineering within the built environment, revealing public awareness, perceived benefits and risks, and attitudes toward genetically engineered microbiomes. Using data from a cross-sectional survey of 1,000 nationally representative U.S. residents over 18 years of age, we examined demographic and cultural factors influencing public sentiment. Results indicate that younger generations report higher knowledge levels, optimism, and perceived benefits of microbiome engineering, while older generations exhibit more caution and concern about risks. Political affiliation, education level, and trust in science also shape public attitudes, with Democrats, college-educated individuals, and those with higher trust in science more likely to view microbiome engineering positively. Notably, nearly half of respondents across demographic groups remain uncertain about the technology’s benefits and risks, and a majority of participants support government oversight to ensure ethical and responsible development. These insights provide a foundation for policymakers and researchers to foster informed public engagement and guide responsible innovation in microbiome engineering for built environments.